2017
DOI: 10.1371/journal.ppat.1006696
|View full text |Cite
|
Sign up to set email alerts
|

Natural killer cell-intrinsic type I IFN signaling controls Klebsiella pneumoniae growth during lung infection

Abstract: Klebsiella pneumoniae is a significant cause of nosocomial pneumonia and an alarming pathogen owing to the recent isolation of multidrug resistant strains. Understanding of immune responses orchestrating K. pneumoniae clearance by the host is of utmost importance. Here we show that type I interferon (IFN) signaling protects against lung infection with K. pneumoniae by launching bacterial growth-controlling interactions between alveolar macrophages and natural killer (NK) cells. Type I IFNs are important but di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
90
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2
2

Relationship

2
6

Authors

Journals

citations
Cited by 61 publications
(105 citation statements)
references
References 69 publications
12
90
0
Order By: Relevance
“…The TLR4-TRAM-TRIF signalling pathway governs type-I IFN production [31], making it relevant to investigate whether the Klebsiella-induced decrease in SUMOylation is mediated by type-I IFN. Further confirming recent findings of our laboratory [32], Kp52145 induced IFNβ, ifnβ and interferon-stimulated genes (ISGs) in wild-type iBMDMs but not in 10 TLR4 -/-( Figure 5D and Supplementary Figure S5A). To demonstrate the contribution of type-I IFN to the Klebsiella-triggered decrease in levels of SUMO-conjugated proteins, we infected BMDMs obtained from IFNAR1 -/mice.…”
Section: K Pneumoniae Induced Decrease In Sumoylation In Macrophagessupporting
confidence: 91%
“…The TLR4-TRAM-TRIF signalling pathway governs type-I IFN production [31], making it relevant to investigate whether the Klebsiella-induced decrease in SUMOylation is mediated by type-I IFN. Further confirming recent findings of our laboratory [32], Kp52145 induced IFNβ, ifnβ and interferon-stimulated genes (ISGs) in wild-type iBMDMs but not in 10 TLR4 -/-( Figure 5D and Supplementary Figure S5A). To demonstrate the contribution of type-I IFN to the Klebsiella-triggered decrease in levels of SUMO-conjugated proteins, we infected BMDMs obtained from IFNAR1 -/mice.…”
Section: K Pneumoniae Induced Decrease In Sumoylation In Macrophagessupporting
confidence: 91%
“…In search for the innate cellular source producing IL‐22 in this model, the authors proposed that a population of lung NK1.1 + NKp46 + CCR6 − cells, defined as NK cells, produce IL‐22 in the lungs postinfection (Figure ), and that NK cell depletion by anti‐asialo GM1 administration decreased IL‐22 mRNA (although not protein) and impaired host defense in the lung . While it is established that lung NK cells are activated and produce IFN‐γ after K. pneumoniae infection, a clear population of IL‐22 expressing lung NK cells was hardly detectable in that study and the effects of NK cell depletion by the use of anti‐asialo GM1 administration on bacterial load and survival of infected mice might rather reflect the decreased expression of IFN‐γ and TNF, that are also protective against K. pneumoniae infection . A recent study confirmed higher susceptibility of Rag2 −/− Il2rg −/− versus Rag2 −/− or wildtype mice as well as a central role for IL‐17 and TNF, but not IL‐22 in the defense against infection with a highly antibiotic resistant strain of K. pneumoniae that is cleared by neutrophil‐independent but monocyte‐dependent mechanisms .…”
Section: Role Of Ilcs In Lung Infection and Ilc Immunitymentioning
confidence: 78%
“…Type I IFNs are the major effector cytokines of the host defense mechanism against viral infections. Recent data indicate that production of type I IFNs also occurs in response to bacteria, and several studies report that type I IFNs are involved in respiratory diseases such as pneumonia, asthma, and sinusitis . IL‐6 is a proinflammatory Th2‐type cytokine that is responsible for the stimulation of fibroblast proliferation and collagen synthesis and is produced by a variety of cells including T and B lymphocytes, macrophages, eosinophils, epithelial cells, and fibroblasts .…”
Section: Discussionmentioning
confidence: 99%